Pengaruh Suhu Evaporasi-Kristalisasi dan Persentase Gula Batu terhadap Warna Produk Serbuk Jahe Merah (Zingiber officinale) - Aprillia, Beauty; Sari, Dessy Agustina (Jurnal Teknologi, 2024)
Red ginger (Zingiber officinale) is recognized as a medicinal plant with multiple benefits. The medicinal benefits of red ginger necessitate cautious handling and treatment to avoid damaging the compounds present in ginger. Producing red ginger powder to make an instant red ginger drink is one of the most frequent methods of ginger processing. The aim of this study is to investigate the impact of raising the temperature during the evaporation-crystallization process (at 80 and 90 oC). Then, the proportion of crystallization agent is rock sugar (at 60 and 100%), which alters the color of red ginger extract, both in terms of research outcomes and commercial products. Each specimen is provided in the form of a solid stage (red ginger powder) and a liquid phase, whereby the red ginger powder is dissolved in hot water (approximately 50 oC). The color of both products was analyzed using a chromameter. The results indicate that the product samples' color changed with the color components L (dark-light), a (red-green), and b (yellow-blue). These changes were caused by an increase or decrease in the amount of dye in the red ginger extract. This caused carotenoids (red) and oleoresin (yellow). Additionally, they indicated a Maillard reaction due to the increase in temperature during the evaporation-crystallization process. The optimum outcomes of this research were observed when fresh raw materials were exposed to 90 °C and 100% cube sugar content. Notably, the color values exhibited no significant discrepancies from those of commercially available red ginger products.